EFFECTS OF N-NITROSODIBUTYLAMINE ON THE LIVER MITOCHONDRIA MORPHOLOGY AND ON THE EXPRESSION OF LIVER MITOCHONDRIAL MEMBRANE SURFACE PROTEINS IN MICE. - Dutta, Sthiti Porna; Jamir, Robin Patnaik; Basaiawmoit, Stephanie Paula; Alam, Anis (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: N-Nitroso-dibutyl amine (DBN) is an established hepatocarcinogen in rodents and its effects on the liver of Swiss albino mice have been examined. The observed alteration in marker enzymes activities indicates hepatic dysfunction and damage to the liver caused by DBN-treatment in mice. This study was aimed to check the carcinogenic effects of DBN exposure on liver mitochondria. Methods: DBN at a dosage of 10 mg kg-1 body weight in 5 % ethanol was administered intravenously weekly for a period of 16 w to induce cancer. Cancer induction was followed by monitoring the activities of marker enzymes such as acetylcholine esterase (AChE), glutathione-S-transferase (GST) and gamma-glutamyl transpeptidase (GGT), which was further supported by the histological examination of liver tissue. Transmission electron microscopy was done to see the alterations in the morphology of the liver mitochondria. Liver mitochondrial membrane proteins were isolated, and proteomic analysis was done. Results: Our preliminary observations indicated significant alterations in the activities of liver marker enzymes [GGT and AChE significantly elevated (<0.025 and<0.0001) whereas GST significantly decreased<0.0001] and in the morphology of liver mitochondria in mice upon DBN exposure. The shape and size of liver mitochondria were found to be highly disrupted and contained large vacuoles, enlarged cristae compartments in comparison to that of the normal control mice. The protein concentration was significantly elevated (<0.0001) in treated mice. The proteomic analysis of the liver mitochondrial membrane surface proteins showed differential expression in DBN-treated mouse compared to that of the normal control[d1]Â . A protein of approximately 14 kDa was found to be overexpressed in the case of DBN treated mice which was seen in a trace amount in normal control. Overexpressed protein was found to be anionic in character. Conclusion: It was evident from the present study that a weekly dosage of DBN with 5 % ethanol for 16 w induces hepatocarcinoma in mice. These results suggested that alterations in the morphology of mitochondria, differential expression of mitochondrial proteins upon DBN exposure are associated with mitochondrial dysfunction in the liver. Keywords: N-Nitroso-dibutyl amine, Hepatocarcinogen, Carcinogenesis, Mitochondrial dysfunction Â